10–3 Use of brief multiprofessional simulation to improve confidence and skills in managing child and adolescent mental health crises out of hours. (17th November 2017) - Lumley, E; Fernando, M; Bahry, R; Bhat, M; Anpananthar, A; Chester, L; Barry, T
Abstract : Background: There is well- established evidence for the benefits of using simulation to improve skills and competence in clinical education. An area of learning need was identified in North East London Foundation Trust (NELFT) to improve confidence and skills in managing out-of-hours CAMHS emergencies, for junior medical trainees initially. A pilot simulation session delivered 6 months earlier to 7 junior medical doctors on psychiatric rotation was well received and showed improved confidence in 4 out of 6 domains evaluated, however it was also recognised that the learning could be augmented by widening participation across disciplines and professions. Aims: To provide and evaluate a multi-professional simulation intended to improve the knowledge and skills of a variety of clinicians working out of hours with young people, including paediatric and mental health doctors, nurses and other allied healthcare professionals. Method: Clinical staff from NELFT (a Mental Health Trust) and Whipps Cross Hospital, (an acute hospital in Barts Health NHS Trust) collaborated to develop the session, comprising an introductory talk and two simulated scenarios, designed to address issues such as capacity, safeguarding, confidentiality and agitation. The training was delivered by a team including a Consultant Paediatrician, Consultant CAMHS Psychiatrist, a Fellow in Medical Education from NELFT and two external actors over 3 hours. The session was evaluated through a pre-session focus group, and pre- and post- session questionnaires. Results: Seven participants attended the session that was delivered; five psychiatry trainees and two paediatric trainees. Different participants were invited to participate in each section of the two scenarios, thereby increasing the number who could have direct experience of the simulation. However, the session had been designed for all participants to learn through observation and discussion. At the end of the session 100% of participants reported feeling confident in on all the outcomes assessed, which was an improvement in all domains. Five out of seven participants stated they would recommend the course to a colleague, enjoyed the course and found that it met their learning needs. Some free text qualitative feedback identified a need for a wider range of topics to be covered, particularly focusing on paediatric learning needs. Conclusions: More work needs to be done in advance of future sessions to recruit from acute paediatric services and encourage nurses and AHPs to attend, in order to have more equal representation within the sessions. Despite this, the evidence from this session and the previous pilot demonstrates that this is an effective, engaging and stimulating way to improve skills and knowledge in this area, and that participants benefit from having the opportunity to share knowledge across disciplines and professions and that collaborative working relationships also develop.